Regulative measures for cybersquatting / Hershan @ Ray Herman, Lydia Salleh and Nur Farhana Said - a, Hershan @ Ray Herman; Salleh, Lydia; Said, Nur Farhana (2012)
There had been a number of researches that investigated on the current situation of cybersquatting or domain name dispute in the world. This study was then conducted in order to investigate the effectiveness of current measure in combating crime of cybersquatting among trade markers in Malaysia. Specifically, this research aimed to highlight the effectiveness of the MYDRP in combating the issue of cybersquatting among trade marker. The primary focus of this research is the protection to the trade markers in online businesses. Weaknesses and strengths of MYDRP Rules and Policy are identified. To gather the needed data, a content analysis and interview were conducted. From the analysis and interviews, the current law, MYDRP, have loopholes and it is insufficient to provide protection to the trade marker's domain name. In conducting our research, we had made comparative studies on the law used to combat cybersquatting in USA, UK, India and Canada with the current measures in Malaysia to address this issue. From the comparisons, we examined why the laws that are used in addressing the domain name disputes in other countries are more effective than the one used in Malaysia. In the light of this problem the government of Malaysia should come out with a new regulative measure in combating cybersquatting as in the USA such as US Anti-Cybersquatting Consumer Protection Act 1999. This in turn benefits the court as it provides the court guidelines in solving the issue of cybersquatting. This also helps in reducing internet fraud as online business will be more protected and secured.